All pins are not created equal: communicating skin cancer visually on Pinterest. Issue 2 (17th April 2018) - Park, Sung-Eun; Tang, Lu; Bie, Bijie; Zhi, Degui
Abstract : Pinterest users are more likely to repin skin cancer related contents that are information-rich or contain certain visual characteristics, depending on the types of skin cancer portrayed. Abstract: Skin cancer is the second most common cancer affecting women younger than 39 years in the USA. As a female-oriented social media, Pinterest could be effectively used in reaching this particular demographic group for the purpose of skin cancer education. We analyze the visual characteristics of skin cancer pins, including use of human image, use of fear-invoking image, pin composition, color, and text legibility. We also explore how these visual characteristics as well as information richness predict Pinterest users' participative engagement. A combination of descriptive and predictive content analysis of 708 pins is conducted. The demographic characteristics of human models are consistent with epidemiology data. Text legibility in bodycopy is low. Information richness is a significant predictor of number of repins in all pins except pins on melanoma with human models. In the case of latter, pin composition, gender of human models, and fear-invoking images were associated with the number of repins. A number of visual characteristics as well as information richness significantly predict Pinterest users' participant engagement with pins on skin cancer. Public health professionals should consider these factors in creating effective prevention messages to be circulated on Pinterest.